Periprostatic adipose tissue (PPAT) supernatant from obese mice releases anticontractile substances and increases human prostate epithelial cell proliferation: the role of nitric oxide and adenosine - Passos, Gabriela Reolon; de Oliveira, Mariana G.; Ghezzi, Ana Carolina; Mello, Glaucia C.; Levi D’Ancona, Carlos Arturo; Teixeira, Simone Aparecida; Muscará, Marcelo Nicolas; Grespan Bottoli, Carla Beatriz; Vilela de Melo, Lucilia; de Oliveira, Eliezer; Antunes, Edson; Mónica, Fabiola Zakia (Frontiers in Pharmacology, 2023)
Prostate gland is surrounded by periprostatic adipose tissue (PPAT) that release mediators that interfere with prostate function. In this study, we examined the effect of obese mice PPAT supernatant on prostate reactivity in vitro and on the viability of human prostatic epithelial cell lines.Methods: Male C57BL/6 mice were fed a standard or high-fat diet after which PPAT was isolated, incubated in Krebs-Henseleit solution for 30 minutes (without prostate) or 60 minutes (with prostate) and the supernatant then collected and screened for biological activity. Total nitrate and nitrite and adenosine were quantified, and the supernatant then collected and screened for biological activity. NOx and adenosine were quantified. Concentration response curves to phenylephrine were obtained in prostatic tissue from lean and obese mice incubated with or without PPAT. In some experiments, PPAT was coincubated with inhibitors of the nitric oxide (NO)-cyclic guanosine monophosphate pathway, adenylate cyclase or with adenosine A2A/A2B receptor antagonists. PNT1-A and BPH-1 human epithelial cells were cultured and incubated with supernatant from PPAT for 24-72 h in the absence or presence inhibitors/antagonists, after which cell viability and proliferation were assessed.The levels of NOx and adenosine were significantly higher in PPAT supernatant (30 min) when compared to the vehicle. A trend toward increase in the levels of NOX were observed after 60 min. PPAT supernatant from obese mice significantly reduced the PE-induced contractions only in prostate from obese mice. The co-incubation of PPAT with inhibitors/antagonists attenuated the anticontractile activity of PPAT supernatant. Incubation with the supernatant of obese mice PPAT significantly increased the viability of PNT1-A cells and attenuated expression of the apoptosis marker, when compared to cells incubated with lean mice PPAT. BPH-1 cells incubated with obese mice PPAT showed greater proliferation after 24-72 h compared to cells incubated with culture medium alone. BPH-1 cell proliferation in the presence of PPAT supernatant was attenuated by NO-signaling pathway inhibitors and by adenosine receptor antagonists after 72 h.NO and adenosine are involved in the anticontractile and pro-proliferative activities of obese mice PPAT supernatant Whether the blockade of NO and/or adenosine derived from PPAT can improve prostate function, more studies are needed.